A Case Study on Some Frequent Concepts in Works of Poetry. (29th August 2019) - Pace-Sigge, Michael
Abstract : This paper looks at a corpus of British and US poetry, uncovering phraseological units which, through their frequency, are indicators of key concepts. Multi-word-units (MWUs) have been discussed extensively with reference to corpus-based research, for example by Sinclair (1996) [2004], Biber and Conrad (1999), or, referred to as formulaicity by Wray (2002); O'Keefe et al. (2007), Greaves and Warren (2010) and Pace-Sigge (2015) describe MWUs preferred in different spoken and written genres. So far, however, there has been very little research in how far MWUs appear in the genre of poetry. A commonly held view is that poetry by definition should not be yielding patterns – it subverts every pattern (linguistically speaking) that it can. Through focus on the main themes surfacing in multiword units, this research looks at usages found in poetic texts in-depth and compares sets of words found with their occurrence patterns in prose literature. Key issues will be highlighted through a number of theme-based case studies, looking at themes of world and sky. Results show that there are common clusters found in poetry and prose corpora: itis depth of usage that marks their divergence.